Role of Social Media in Socioeconomic Development: Case of Facebook - Amrouche, Nawel; Hababou, Moez (Review of Economic Analysis, 2022)
To study the role of Information and Communication Technology (ICT) on countries’ socioeconomic development, the paper investigates the case of Facebook penetration on improving their standing as measured via GNI per capita PPP (Gross National Income per capita based on purchasing power parity). We use four macro factors categories (political, economic, demographic, and technological) in addition to Facebook penetration per capita in order to measure the potential influence of various factors on the socioeconomic level of countries. While the analyses of ICT effect on development has been the focus of many papers in the past, the specific analysis of social media is scarce. Compared to previous studies investigating social media role, we use a large dataset covering all classes of countries and examine holistically many types of determinants using different models. In addition, we distinguish our paper using the economic classification of countries according to the World Bank. Our study indicates that Facebook penetration has a significant positive role on the socioeconomic level of countries, but such role varies depending on the countries’ classification level. Besides, there is a decreasing marginal effect showing the importance for policy makers to assess the complex dynamic behind the characteristic of each country.